Peran Guru Pedidikan Agama Islam dalam Meningkatkan Perilaku Beribadah Siswa: Studi Kualitatif Naturalistik di SMA Negeri 2 Kota Bekasi - Ahmad Tsani; M. Sabeni (Turats, 2015)
The problems of this study were (1) Role of Islamic education teachers in improving the behavior of the student worship, (2) factors that support and hinder worship in improving student behavior. In this study the authors used qualitative research naturalistic. The methods used in data collection techniques are observation, interviews, and documentation. From research conducted, the authors found that the role of Islamic education teachers in improving the behavior of the student worship, namely as an educator, a motivator, innovator, acting as a parent, and must be able to position ourselves as facilitators and mentors. The factors that support in improving student behavior is worship of adequate infrastructure, power builder that support, intra or extra-curricular activities, and of course a good relationship with the parents. As the inhibiting factors include negative current urban culture, and lack of parental supervision of the activities their children do in an effort to improve the behavior of worship.